2021
DOI: 10.1080/08985626.2021.1914741
|View full text |Cite
|
Sign up to set email alerts
|

Crafting growth together

Abstract: There is a re-positioning of entrepreneurship towards the sustaining, the frugal, the local, and the everyday. This poses challenges for peripheral policy work, especially around growth, at sectoral and regional levels. Through collaborative workshops with engaged craft brewing stakeholders, this study generated deep new insights into how diverse forms of value can come to be created, shared, stewarded, invested in, grown, given away, and held as a collective resource, in order to both sustain community, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 91 publications
(91 reference statements)
0
15
0
Order By: Relevance
“…Based on the Sicilian CB industry, Alfeo et al (2020) identified three business models in the CB market: microbrewery, brew-pub and beer firm. These businesses use distinct market approaches and usually sustain community, helping to build sectoral growth (Dodd et al, 2021). They can also play a relevant role in promoting certain regions and countries (Bachman et al, 2021;Alonso et al, 2021).…”
Section: Qualitative Cluster Analysismentioning
confidence: 99%
“…Based on the Sicilian CB industry, Alfeo et al (2020) identified three business models in the CB market: microbrewery, brew-pub and beer firm. These businesses use distinct market approaches and usually sustain community, helping to build sectoral growth (Dodd et al, 2021). They can also play a relevant role in promoting certain regions and countries (Bachman et al, 2021;Alonso et al, 2021).…”
Section: Qualitative Cluster Analysismentioning
confidence: 99%
“…Creative tools from new technologies are needed to help commercialize crafts. Urgent repositioning for frugal people's efforts, maintaining a sense for progress and socio-economic and policy growth (Dodd et al, 2021). Cooperation is needed in the idea of compatibility in completing the deficiencies in the work process (Thurnell-Read, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…This included supplying distributors and customers across the UK and overseas as well as diversifying their businesses to tap into growth opportunities in the related gastronomy and leisure sectors (Ellis and Bosworth, 2015). Globally, the craft brewery market has been growing based on local ingredients, place embeddedness and entrepreneurial strategies to differentiate from, rather than compete directly with multinational producers (Argent, 2018;Dodd et al, 2021).…”
Section: Craft Breweries In the Uk: An Overviewmentioning
confidence: 99%
“…This included supplying distributors and customers across the UK and overseas as well as diversifying their businesses to tap into growth opportunities in the related gastronomy and leisure sectors (Ellis and Bosworth, 2015). Globally, the craft brewery market has been growing based on local ingredients, place embeddedness and entrepreneurial strategies to differentiate from, rather than compete directly with multinational producers (Argent, 2018;Dodd et al, 2021). Capturing what Sj€ olander-Lindqvist et al (2020) refer to as "social terroir", entrepreneurs in this sector are "rooted and shaped by the specific cultural features that are associated with the region's identity" (2020, p. 158).…”
mentioning
confidence: 99%